PENGARUH KETERLIBATAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT IBU DAN ANAK MILANO TELUK KUANTAN - ", Gusmarni; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aimed to analyze the job involvement and organizational commitment and influence the performance of employees at RSIA Milano Teluk Kuantan. Involvement as variable (X1), Organizational commitment as a variable (X2), and employee performance as a variable (Y). The method in this research is descriptive and quantitative using SPSS 23, where in the samples used are 40 employees who conducted the census and data collection through questionnaires. The results of the analysis using the validity, reliability, determination test, simple linear regression, multiple linear regression test t, and test F. It can be concluded that work engagement significantly influence performance of employees at RSIA Milano Teluk Kuantan, that organizational commitment significantly influence the performance of employees at RSIA Milano Teluk Kuantan, and job involvement and organizational commitment significant effect on the performance of employees at RSIA Milano Teluk Kuantan.Keywords : Job Involvement, Organizational Commitment, and Employee Performance